Pengaruh Rasio Keuangan Terhadap Financial Distress Pada Perusahaan Ritel Yang Terdaftar Di Bursa Efek Indonesia - Bagas Hanggara; Anita Handayani (Universitas Muhammadiyah Gresik, 2020)
This study aims to examine the effect of financial ratios on financial distress on retail companies listed on the Indonesia Stock Exchange (IDX) for the period 2014-2018. Sampling was carried out using the purposive sampling method. The sample used is the financial statements of retail companies listed on the Indonesia Stock Exchange a with total of 40. Testing is done using logistic regression. The results showed that the Current Ratio variable influenced and negatively affected financial distress. Return On Assets has no effect and is positive for financial distress. While the Debt to Equity Ratio and Total Asset Turn Over variables have no effect and are negative for financial distress. The conclusion that the current ratio variable influences and negatively affects financial distress. The return on asset variable has no effect and is positive for financial distress. The variable Debt to Equity Ratio and Total Asset Turn Over has no effect and is negative for financial distress. Next researcher is to make the Current Ratio (CR) variable as a mediating variable between X variables, namely Return On Assets (ROA), Debt to Equity Ratio (DER) and Total Asset Turn Over (TATO) with Y variable, namely financial distress